The Impact of Dictionary.Com Application on Vocabulary Acquisition for Diploma Students - Aziz , Safiyahbinti Abdul (International Journal of Psychosocial Rehabilitation, 2020)
English language learning is very challenging to second language learner especially in vocabulary acquisition, with the increase in the use of smartphone, it is hope there are new pedagogical implication in teaching voabulary. This study focusing on the impact of Dictionary.com android application for diploma students. To conduct this research 100 students of Culinary Programme from KPYPJ were devided equally into treatment and control group to undergo a pretest be consisting of 40 objective question on Academic Word List (AWL). The treatment group had learn the Academic Word List using Dictionary.com android application using their own mobile phone while the control group will learn using the traditional method for seven week followed by the pre- test. Two interview sessions were conducted to get the feedback on Dictionary.com application from the lectures and the students. The use of Dictionary.com application showed the positive impact based on the result of the pre and post-test, as it rejects the null hypothesis. Furthermore, the Treatment Group showed better results as compared to the Control Group in the Post-test. Dictionary.com application that used for the treatment group received good feedbacks from the lecturers as it aids in teaching vocabulary especially the pronunciation with provided correct spelling and interesting way of teaching vocabulary. In addition, the application is user friendly and able to motivate the student in learning new vocabulary. The main conclusion drawned from the research is Dictionary.com is effective in assisting vocabulary learning for KYPJ diploma students.